Effect of Terracing on Upland Crops - Mirchandani, PM (Journal of Soil and Water Conservation, 2022)
Bench terraces have been in use for many centuries. They are constructed for making paddyfields and for faci- litating agricultural operations on steep slopes. Extensive areas with moderate slopes are under cultivation where controlling the flow of surface runoff is necessary for the protection of the lands. Here two types of terracesl are in general use — the level or ridge type absorptive terrace ) and graded or broad channel type ( drainage terrace ). Both types have a ditch or a channel with a ridge below. Level terraces are constructed without grade and impound surface runoff for increased absorption. Graded channel terraces are constructed with a slight grade. They stop straight down the hill runoff, in- crease absorption and carry the excess water to an adequately protected disposal area.Preliminary studies conducted at Deo- chanda Experiment Station of Damodar Valley Corporation showed that Level terraces ( contour bunds ) reduced the yields of upland crops and as such were not suitable for the uplands of the region. Graded chan- nel terraces were thus indicated for the region. In so far as very few data were available regarding the effect of vanow, terraces on biological growth, it was felt a study to see the effect on upland crops the various terraces that can be easily constructed should give the best results for evolving a suitable terrace for the uplands of the region. Since the Level terrace reduced yields, it was felt that an opening in the Level terrace for draining away some of the im- pounded water should improve yields. The farmers of the region prefer Bench terraces and are good at constructing the same. Two modifications of the Bench terrace namely, Bench terrace with open ends and Bench terrace graded with open ends were included in the study. This paper presents the constructional details of the five named terraces as also the three years' results of the study conducted at Deochanda Experiment Station to evaluate their effect on the yield of Gora paddy, maize and groundnut.